2020
DOI: 10.1039/d0fo00004c
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and comparison of the properties of Scy p 9, aScylla paramamosainallergen

Abstract: This study investigated the properties of Scy p 9 in mud crab (Scylla paramamosain).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Arginine kinase is a 41 kDa phosphagen kinase that plays an important role in cellular energy metabolism in invertebrates. Apart from these two major allergens, sarcoplasmic calcium-binding protein, triosephosphate isomerase, pyruvate kinase 2, myosin light chain I and filamin C were minor crab allergens ( 56 , 67 , 68 ). Jasim et al ( 69 ) identified three common crab allergens including tropomyosin, arginine kinase and actin as well as a novel allergen hemocyanin from S. transquebarica that is commonly consumed in Malaysia.…”
Section: Prevalence and Natural History Of Seafood Allergy In Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Arginine kinase is a 41 kDa phosphagen kinase that plays an important role in cellular energy metabolism in invertebrates. Apart from these two major allergens, sarcoplasmic calcium-binding protein, triosephosphate isomerase, pyruvate kinase 2, myosin light chain I and filamin C were minor crab allergens ( 56 , 67 , 68 ). Jasim et al ( 69 ) identified three common crab allergens including tropomyosin, arginine kinase and actin as well as a novel allergen hemocyanin from S. transquebarica that is commonly consumed in Malaysia.…”
Section: Prevalence and Natural History Of Seafood Allergy In Asiamentioning
confidence: 99%
“…Summary of shellfish and fish allergens. kinase 2, myosin light chain I and filamin C were minor crab allergens(56,67,68). Jasim et al(69) identified three common crab allergens including tropomyosin, arginine kinase and actin as well as a novel allergen hemocyanin from S. transquebarica that is commonly consumed in Malaysia.…”
mentioning
confidence: 99%
“…The reason for this is that the hydrophobic tail carried by SDS allows it to enter the interior of the ATM molecule and destroy the hydrophobic effect, exposing the hydrophobic region of the whole protein molecule. 26 He et al 38 reported that the allergenicity of an allergen increased with increasing hydrophobicity. These findings further proved that there was an intermolecular disulfide bond in ATM and indicated that the linear epitope played a major role in the IgE-binding capacity of ATM.…”
Section: Discussionmentioning
confidence: 99%
“…Other registered shellfish allergens that have been identified at the molecular level include arginine kinase (AK), myosin light chain (MLC), troponin C (TnC), hemocyanin (Hc), triosephosphate isomerase (TIM), fatty acid-binding protein (FABP) and the newly identified 98kDa glycogen phosphorylase (GP) from shrimp [16,17,18 ▪ ]. Filamin C and paramyosin from are on the other hand identified from mud crab ( Scylla paramamosain ) and veined rapa whelk ( Rapana venosa ) respectively [19 ▪ ,20 ▪ ]. By means of inhibition ELISA, Yu et al [21 ▪▪ ] showed that paramyosin played an important role in molluscan and mite-molluscan cross-reactivity, and the relevance of these proteins in other edible shellfish would warrant more characterization.…”
Section: Introductionmentioning
confidence: 99%